The Analysis of Customer Satisfaction of Chengdu ReadKing Advertising Decoration Engineering Co., Ltd. - Wang, Dong; Tantasanee, Somchai (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
Customer satisfaction is one of the important factors affecting organizational performance. There are five dimensions to investigate customer satisfaction which are tangible, reliability, responsiveness, assurance, and empathy. Chengdu ReadKing Advertising Decoration Engineering Co., Ltd. was selected as an example to analyze the situation of the five dimensions of customer satisfaction. The purpose of the study is to analyze the customer satisfaction and evaluate the current situation of customer service in 2021. The sample size is randomly 100 customers from Chengdu ReadKing Advertising Decoration Engineering Co., Ltd. A mixed research method combining quantitative and qualitative research was adopted. The descriptive analysis and Multiple Linear Regression were applied with the interview as the quantitative and the qualitative analyses. The result shows that assurance, responsiveness, and empathy are the significant variables which influenced the customer satisfaction. The strongest influence toward the satisfaction is assurance following by responsiveness and empathy respectively.